Windows Server 70-741 : networking with Windows Server 2016 (Pearson IT Certification, 2017)
"This engaging, self-paced video course includes demonstrations and configurations of various features of Windows Server 2016. Even if you're not planning to take the 70-741 exam, this video training will help you get up to speed on the new and updated features related to networking with Windows Server 2016. Throughout each lesson, IT trainer and technical author Andrew Warren describes key concepts and puts them into action with demonstrations and real-world scenarios. Follow along by creating your own practice environment using virtual machines. By the end of the course, you should have learned enough to support your organization's Windows Server 2016 network infrastructure and to take the 70-741 Networking with Windows Server 2016 exam."--Resource description page